Photodegradation of organic pollutants in aqueous solutions caused by Fe(OH)aq2+ photolysis: Evidence of OH radical formation - I. P. Pozdnyakov; Yu. A. Sosedova; V. F. Plyusnin; E. M. Glebov; V. P. Grivin; D. Yu. Vorobyev; N. M. Bazhin (International Journal of Photoenergy)
Photochemistry of Fe(III) hydroxocomplexes has a great interest because of possibility of hydroxyl radical formation at the primary photochemical step. This mechanism is based mainly on the analysis of the final products of photochemical reactions between light-excited Fe(III) complexes and organic compounds. However, realization of an alternative mechanism of photolysis, based on the intermolecular electron transfer from organic molecules located in the second coordination sphere to the light-excited complex could take place. To distinguish these mechanisms, the experiments on the nanosecond laser flash photolysis of Fe(OH)aq2+ in water solutions (pH 3) with organic additives; namely nitrobenzene, N,N-dimethylformamide, and phenol have been performed. And the formation of the organic radicals Ph(•OH)NO2, HCON(CH2•)(CH3), and Ph(OH)2•, was observed, respectively. The rate constants of the formation and decay of the radicals coincide with those found in literature. The results support the formation of the hydroxyl radical upon the photolysis of Fe(OH)aq2+.